Detection system of smart sprayers: Status, challenges, and perspectives - Hong, Sun; Minzan, Li; Qin, Zhang (International Journal of Agricultural and Biological Engineering, 2012)
A smart sprayer comprises a detection system and a chemical spraying system. In this study, the development status and challenges of the detection systems of smart sprayers are discussed along with perspectives on these technologies. The detection system of a smart sprayer is used to collect information on target areas and make spraying decisions. The spraying system controls sprayer operation. Various sensing technologies, such as machine vision, spectral analysis, and remote sensing, are used in target detection. In image processing, morphological features are employed to segment characteristics such as shape, structure, color, and pattern. In spectral analysis, the characteristics of reflectance and multispectral images are applied in crop detection. For the remote sensing application, vegetation indices and hyperspectral images are used to provide information on crop management. Other sensors, such as thermography, ultrasonic, laser, and X-ray sensors, are also used in the detection system and mentioned in the review. On the basis of this review, challenges and perspectives are suggested. The findings of this study may aid the understanding of smart sprayer systems and provide feasible methods for improving efficiency in chemical applications. Keywords: smart sprayer, target detection, weed control, disease detection, chemical application DOI: 10.3965/j.ijabe.20120503.002 Citation: Sun H, Li M Z, Zhang Q. Detection system of smart sprayer: Status, challenges, and perspectives. Int J Agric & Biol Eng, 2012; 5(3): 10